The archaeology of ethnicity - Jones, Siân, 1968- (London ; New York)
xiii, 180 sayfa
Keywords: “The question of ethnicity is highly controversial in contemporary archaeology. Indigenous and nationalist claims to territory, often rely on reconstructions of the past based on the traditional identification of 'cultures' from archaeological remains. Sian Jones responds to the need for a reassessment of the ways in which social groups are identified in the archaeological record, with a comprehensive and critical synthesis of recent theories of ethnicity in the human sciences. In doing so, she argues for a fundamentally different view of ethnicity, as a complex dynamic form of identification, requiring radical changes in archaeological analysis and interpretation” --